The Effect of Addition of Powder Areca Nut Midrib on Polyester Matrix to the Tensile and Bending Strength - Hendriwan Fahmi; Putri Pratiwi; Tri Maryanto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2020)
In this life, humans certainly need a variety of equipment called material. In its development the material continues to experience progress as in early life, humans only use equipment made from simple materials such as wood, stone and others. Then move to the metal and the last to use a lot of mixture in the refinement of these materials, one form of mixed material created by humans is composite. Betel nut has a lot of powder, how to take it without damaging the areca nut plant. After the extraction of powder is applied to the areca nut, the fiber will be mixed with polyester resin as its matrix. Polyester resin is a matrix of composites. This resin is also included in thermoset resin. In the thermoset polyester the liquid resin is converted into hard and brittle solids formed by chemical cross-bonds that form very strong polymer chains. The mixture will produce composite materials which have different mechanical properties and characteristics from the forming material. Composite materials have the properties of conventional materials from the manufacturing process through inhomogeneous mixing. The purpose of this study was to determine the effect of adding areca nut powder to the polyester matrix on tensile and bending strength. Research and testing are carried out in several stages, including the manufacture of specimens. Both materials are stirred manually until both materials are fused evenly, then tensile and bending tests are carried out, data analysis and conclusions. The results of this research got the best tensile test values on composite polyester resin specimens and areca nut powder with a composition of 90%: 10% with a value of 5.09 MPa. And the results of bending which got the best bending test values are polyester resin composites and nutmeg powder with a composition of 90%: 10% with bending test values of 3.77MPa.